2018
DOI: 10.18280/mmep.050410
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance amelioration of flat plate solar collector of an indirect dryer

Abstract: Article presents an experimental investigation for the comparison of thermal performance of three different configurations flat plate solar collector. These flat plate solar collectors consist of glass cover and aluminium absorber plate which is painted with black paint. The edge and bottom surfaces are thermally insulated with a polystyrene layer for the first configuration, a polystyrene layer covered with a sheet of aluminium paper for the second one and a polystyrene layer covered with a sheet of aluminium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This method ensures that the system's costs are reduced to the absolute minimum without putting the supply in jeopardy. The findings of the research indicate that the costs associated with utilizing a solar wind hybrid system are significantly lower than the expenses associated with using individual wind and solar systems [9,10]. According to the findings of a recent study, it is possible to construct an independent hybrid energy system using solar panels, wind turbines, and batteries.…”
Section: Introductionmentioning
confidence: 97%
“…This method ensures that the system's costs are reduced to the absolute minimum without putting the supply in jeopardy. The findings of the research indicate that the costs associated with utilizing a solar wind hybrid system are significantly lower than the expenses associated with using individual wind and solar systems [9,10]. According to the findings of a recent study, it is possible to construct an independent hybrid energy system using solar panels, wind turbines, and batteries.…”
Section: Introductionmentioning
confidence: 97%
“…By comparing results for collectors with and without PCM, it was found that the use of PCM increases thermal energy of the collector, as well as using transverse obstacles with wax, which contributes to enhance thermal efficiency compared with collector using wax without fins. Three types of flat plate solar collectors have been studied experimentally by Blaise et al [14]. The results showed that the use of baffles with flat plate solar air collectors significantly improves the thermal efficiency, as well as increases the air temperature outside the collector.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is referred that as a development of three plants Andasol (50 MW) by Solar Millennium and located in southern Spain [3], Solana 280 MW in Arizona [2] and Shams-1 station (100 MW) in Abu Dhabi. The facility discussed in this paper is a 30 MW SEGS VI plant, which was established in 1988 by Luz International Ltd, which is located in the Mojave Desert in southern California [4].…”
Section: Introductionmentioning
confidence: 99%